Vertical Housing Development, on Control Regional Bali Regulation of Building Height - Dharmayanty, Ni Luh Putu Dessy; Paturusi, Syamsul Alam; Dwijendra, Ngakan Ketut Acwin; Dewi, Ni Ketut Agusinta (International Journal of Engineering and Emerging Technology; Vol 4 No 2 (2019): July - DecemberDO - 10.24843/IJEET.2019.v04.i02.p03, 2020)
Abstract Regional Regulation of the Province of Bali concerning the height of buildings has been known since 1974 until now. The development of tourism has an impact on the high price of land in Bali especially in urban areas and tourist accommodation. The increase in the number of urban residents and the high number of shortages of decent housing, opens a discourse on Vertical Housing development, through the National program that has been started since 2011. The development of Vertical Housing in Bali has not been responded to optimally by both the Regional Government and the Community. However, the need for housing and various other factors are increasing and unresolved with existing programs, therefore or unwillingly or dislike of the people of Bali must prepare themselves to be able to receive Vertical Housing development in the Urban area. Then how is this Regulatory Control related to the program? Then how far is the effect? Through this research, this will be traced qualitatively.   Keywords — Proper Residential Needs , Regional Regulations, Vertical Housing .